2010
DOI: 10.1152/jn.00188.2010
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Electroencephalography in Freely Moving Mice

Abstract: Choi JH, Koch KP, Poppendieck W, Lee M, Shin HS. High resolution electroencephalography in freely moving mice. J Neurophysiol 104: 1825-1834, 2010. First published July 7, 2010 doi:10.1152/jn.00188.2010. Electroencephalography (EEG) is a standard tool for monitoring brain states in humans. Understanding the molecular and cellular mechanisms underlying diverse EEG rhythms can be facilitated by using mouse models under molecular, pharmacological, or electrophysiological manipulations. The small size of the mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 45 publications
(43 reference statements)
1
67
0
Order By: Relevance
“…In particular, in GAERS and WAG/Rij 83,84, as well as in humans 18,19, there is evidence of a cortical initiation site. Whether this is the case in the GHB model remains to be ascertained, although there is some evidence that, within the cortex, seizures are initiated in the primary somatosensory cortex 143. In addition, in GAERS, intracellular or extracellular recordings from thalamic and cortical neurons have provided a clear view of their firing dynamics during ASs, in vivo 83,144,145, whereas a similar description is not available for GHB-elicited ASs.…”
Section: Mechanism Of Ghb-induced Ass In the Ratmentioning
confidence: 99%
“…In particular, in GAERS and WAG/Rij 83,84, as well as in humans 18,19, there is evidence of a cortical initiation site. Whether this is the case in the GHB model remains to be ascertained, although there is some evidence that, within the cortex, seizures are initiated in the primary somatosensory cortex 143. In addition, in GAERS, intracellular or extracellular recordings from thalamic and cortical neurons have provided a clear view of their firing dynamics during ASs, in vivo 83,144,145, whereas a similar description is not available for GHB-elicited ASs.…”
Section: Mechanism Of Ghb-induced Ass In the Ratmentioning
confidence: 99%
“…Pharmacologically-evoked absence seizures in mice have been produced through the systemic administration of GABA A R antagonists and GABA B R agonists. None of the experiments that used these drugs suggested a sex-dependent phenotype; the studies were either reported without specifying mouse sex or were performed using only males or females without a stated rationale (Aizawa et al, 1997; IIshige et al, 1996; Weiergraber et al, 2008; Zaman et al, 2011; Choi et al, 2010). …”
Section: Sex Differences In Mouse Models Of Typical and Atypical Absementioning
confidence: 99%
“…Patterns of brain responses triggered by stimuli called event related potentials (ERPs) can be measured on the scalp electroencephalogram in both humans and mice and serve as a neurophysiological outcome measure for abnormal information processing (Choi et al , 2010; He et al , 2001; Olichney et al , 2010). Direct in vivo neurophysiolgoical recording has become more readily accessible in mice to evaluate the firing patterns of cells across brain regions during task performance ( cf.…”
Section: Behavioral Phenotyping Strategiesmentioning
confidence: 99%